Political and Constitutional Thought Sami FrashÃ«ri - Sherifi, Elmaz (Mediterranean Journal of Social Sciences, 2012)
Sami FrashÃ«ri is one of the most erudite Albanian minds of XIX century Albania. Born in Frasher, Permet on June 1st, 1850,Sami, an Ottoman citizen, stated "I am an Albanian," and in some of the articles in the newspaper "Sabah" (Morning gazette), rejectedthe thesis that Albanian Muslim were Turkish and Albanian Orthodoxy were to be treated as Greek. Through such terms he helped indifferentiating the terms Turkish and Muslim, and not to be recognized as synonyms. He was known as a reporter and editor, creator ofliterature and of scientific works, but I believe that his deep political opinion is recognized in his non-political works. Beginnings of thepolitical thought are given in his political drama of 1874, Besa yahud Ahde Vefa (Honoring the Promise), where loads of high emotionalartistic tools, "hide" political goals. "Besa" (Promise) is treated, not as the rate of a customary to justice, but as the value of theconstitution and faithful soul for the new "homeland." The vocabulary entitled "al-laam Kamus", can be considered a political commentaryon Albania and Albanians. The other vocabulary of Turkish normative linguistics "Kamus-i Turki", explains the words, Arnavud(Albanian), ArnavudÃ§a (Albanian) Arnavudluk (Albania). Sami defines the terms Arnavudluk as the nation or nationality, which isAlbanian and place (memleket) of Albania, which consists of four majorities. Political thought and constitutional dimension appears to"What Albania was, what is and what will become?" In this writing lies the thought of the establishment of political institutions designedaccording to principles of Montesquieu. The legislative body was called the General Council. The form of government was according toRepublican ideology, under the Head of State collegial, which he described as Strabonious, "Wise Men Councilâ€, and an executivepower, with seven ministries. Judiciary was established in three divisions. The political, natural boundaries coincided with the fourvilayets. Albania was divided into 15 administrative units, which he called "plots", with 15 of their capitals and the capital of Albania,which would have been SKENDERBEGAS. Political project of Sami FrashÃ«ri was associated with a Draft Budget, the structure of stateadministration and their salaries, according to functions. Aim of Study: Enriching the political "Fund" of Albanian political elite, withpolitical thought and constitutional dimension of Sami Frasheri. Survey Methodology: Finding the political thought of Sami Frasherithrough his artistic, scientific and academic writings. Analysis of political project "Albania, what was, what is and what will become?â€ inorder to reveal the dimension of constitutional thought. Comparing between local and foreign authors and the narrative description ofdeductions, to prove the hypothesis.